Dynamics of changes in Russian verbal paradigm under the influence of secondary imperfectivation - Timur I. Galeev; Vladimir V. Bochkarev; Valery D. Solovyev (Russian Language Studies, 2025)
The relevance of the study is determined by the fact that the variability of aspectual affixes in the Russian language has not been fully studied. Meanwhile, super-large diachronic corpora of texts provide the opportunity of a detailed quantitative description of verbal affixes evolution. The aim of the study is to identify objective syntagmatic and paradigmatic factors (extrasyllabic synharmonicity, word morphological structure evolution, lexical compatibility, style) that determine the choice of one of the competing suffixes among variable verbs with the redundant paradigm with secondary imperfection -a-(-ya-)/-yva-(-iva-) . The authors used the Russian language corpus of the Google Books Ngram corpus, including data on the word forms frequency over the past 200 years. The authors used methods of corpus analysis and diachronic quantitative analysis. The study revealed psychophonetic, morphological, semantic, and stylistic factors affecting the linguistic changes of redundant verbal paradigms. The authors came to the conclusion that, contrary to popular belief, the former na -a-(-ya-) variant is not replaced with the -iva-(-yva-) form in most cases; according to frequency dynamics, a temporary increase in the popularity of forms of secondary imperfection in general was followed by a return to the primary forms of Imperfect in recent decades. In rare cases, where a form with a suffix denoting iteration is approved, the form was chosen because of the root vowel, “l-epenteticum”, and verb prefixes. The frequency and prevalence of the verb hypothetically preventing the emergence of variants or unification had no effect on language changes. The developed approach can be applied to study evolution of competing word forms in a wide range of cases.